Production of Composite Cement Clinker Based on IndustrialWaste - Kuandykova, A.; Taimasov, B.; Potapova, E.; Sarsenbaev, B.; Kolesnikov, A.; Begentayev, Begentayev; Kuldeyev, E.; Dauletiyarov, M.; Dauletiyarov, N.; Amiraliyev, B.; Abdullin, A. (Compos. Sci., 2024)
The possibility of producing cement clinker using low-energy, resource-saving technologies is studied. The composition of industrial waste for low-energy-intensive production of Portland cement clinker at factories in Southern Kazakhstan is analyzed. The possibility of replacing the deficient iron-containing corrective additive with “Waelz clinker for zinc ores” is shown. “Waeltz clinker from zinc ores” as part of the raw material charge performs several tasks: it is a ferrous corrective additive, works as a mineralizer for clinker formation processes, introduces coal into the charge and allows one to reduce the consumption of natural fuel. The processes of burning raw mixtures, wholly or partially consisting of industrial waste, are completed at 1350 ◦C. This reduces the consumption of main burner fuel for clinker burning and reduces CO2 emissions into the atmosphere. High-quality cement clinker is obtained based on raw material mixtures withWaeltz clinker from zinc ores from the Achisai Metallurgical Plant, phosphorus slag, coal mining waste from Lenger mines and sodium fluoride. The phase composition and microstructure of low-energy clinkers are revealed. Involving industrial waste in raw material circulation will reduce environmental pollution and improve the environment.
Keywords: Portland cement clinker; roasting; industrial waste; zinc ore; “Waeltz clinker from zinc ores”; fuel consumption; environmental engineering; composite materials